2009
DOI: 10.1111/j.1744-7917.2009.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐nickel insects and nickel hyperaccumulator plants: A review

Abstract: Insects can vary greatly in whole-body elemental concentrations. Recent investigations of insects associated with Ni hyperaccumulator plants have identified insects with relatively elevated whole-body Ni levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 47 publications
0
47
0
1
Order By: Relevance
“…Nevertheless, extensive insect herbivory damage to all Ni hyperaccumulator species in Sabah was observed during this study. Specialist insect herbivores may feed on Ni hyperaccumulators without negative effects (Boyd 2009), and one geometric moth species (Erebidae: Erebinae tribe Poaphilini) has been found in this study to feed exclusively on the Ni hyperaccumulator Phyllanthus balgooyi (illustrated in Fig. 3, top).…”
Section: Interaction Of Ni Hyperaccumulators With Insect Herbivoresmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, extensive insect herbivory damage to all Ni hyperaccumulator species in Sabah was observed during this study. Specialist insect herbivores may feed on Ni hyperaccumulators without negative effects (Boyd 2009), and one geometric moth species (Erebidae: Erebinae tribe Poaphilini) has been found in this study to feed exclusively on the Ni hyperaccumulator Phyllanthus balgooyi (illustrated in Fig. 3, top).…”
Section: Interaction Of Ni Hyperaccumulators With Insect Herbivoresmentioning
confidence: 98%
“…The 'Elemental Herbivory Defense' hypothesis (Boyd and Martens 1998;Boyd 2009) suggests that high Ni loading in the leaves of Ni hyperaccumulators could result in reduced (insect) herbivory attack. However, field observations on Mount Bloomfield, Palawan (Philippines), showed that Ni hyperaccumulators did not experience less herbivory (Proctor et al 2000), and the Ni hyperaccumulator Shorea tenuiramulosa suffered as much foliar herbivory damage as 'normal' plant species growing in the area on Mount Silam in Sabah (Proctor et al 1989).…”
Section: Interaction Of Ni Hyperaccumulators With Insect Herbivoresmentioning
confidence: 99%
See 1 more Smart Citation
“…There is indeed evidence that ecological partners of hyperaccumulators have evolved resistance to the hyperaccumulated element. For example, Boyd (2009) reported insects that feed almost exclusively on Ni hyperaccumulators. He identified 15 insect species across three (sub)orders that can tolerate an internal Ni concentration of ≥500 mg/kg −1 .…”
Section: Is There Co-evolution Of Hyperaccumulators With Ecological Pmentioning
confidence: 99%
“…Beetles were killed immediately after collection and then dried at 65 o C for 72 h. Analyzing insects immediately after collection means that metal in the gut contents will be included in the measurements (Migula et al, 2007), yet whole-body measurements that include gut contents are relevant measures of the metal dose received by a predator that consumes entire insect prey (Boyd, 2009). Four composite samples of dried beetles were analyzed for their whole-body metal concentrations (Wall & Boyd, 2002).…”
Section: Whole-body Metal Concentrations Of Chrysolina Clathratamentioning
confidence: 99%